Establishing the correlation of negative permittivity and AC conductivity of La2−xSrxNiO4 (x = 0, 0.1, 0.3, 1.0) for microwave shielding applications - Katheriya T.; Nirala G.; Upadhyay S. (My University, 2025)
Negative permittivity, a phenomenon observed in certain materials, has attracted considerable interest because of its significant implications in various fields of physics and engineering. Herein, from the perspective of intrinsic properties of single-phase materials, a few compositions of the La2−xSrxNiO4 system (x = 0, 0.1, 0.3, 1.0) were synthesized using the solid-state reaction method. XRD studies showed that the solubility limit of Sr in the lattice of La2NiO4 is limited (0.3 < x < 1.0). Morphological studies have revealed that average grain size and density increase with increasing Sr content. Dielectric/electrical properties were studied across a wide frequency range (20 Hz-2 MHz) and at higher temperatures (30-600 °C). All the samples have negative dielectric constant and this is attributed to plasma oscillation. The Drude model was fitted to experimental data and parameters like plasma frequency (ωp) and relaxation frequency (ωτ) were determined. The low value of activation energy (<0.05 eV) for direct current (D.C.) conduction and an increasing trend in relaxation time (τ) with temperature suggest a “small-polaron hopping conduction” mechanism. Studies on complex plane impedances have shown positive reactance and increased inductance with Sr-doping. Microwave shielding analysis revealed reflection as the primary shielding mechanism. The composition with x = 0.30 having high dielectric constant and conductivity shows the best shielding capabilities. These findings highlight the ability to tune the negative dielectric properties of La2NiO4 through compositional adjustments, which is significant for applications such as microwave shielding and coil-less inductive materials for future devices. © 2024 The Royal Society of Chemistry.